Partial linearization and partial decoupling of non‐invertable impulsive extensions - Sermone, Lelde (Mathematical Modelling and Analysis, 1998)
A problem of a partial linearization and partial decoupling of non‐invertable impulsive extensions is considered. The sufficient conditions for the dynamical equivalence are given.First Published Online: 14 Oct 2010